Small millets in India: Current scenario and way forward - Hariprasanna, K (Indian Farming, 2023)
In India, sorghum (Sorghum bicolor), pearl millet (Pennisetum glaucum) and a group of seven small millets together constitute the millets family. The group of small millets includes finger millet (Eleusine coracana), little millet (Panicum flexuosum), kodo millet (Paspalum scrobiculatum), foxtail millet (Setaria italica), barnyard millet (Echinochloa frumentacea), proso millet (Setaria italica) and browntop millet (Brachiaria ramosa). These crops, known by different names in local languages have traditionally been the vital component of dry farming and hill agriculture systems in India supporting millions of poor and food insecure people.